Principle of autonomy in letter of credit (LC) - An overview from legal and Shariah perspective - Othman, Ahmad Azam; Che Hashim , Rosmawani (2013)
The issuance of letter of credit (LC) as a method of payment in international trade carried by itself its distinctive feature that is independent from the underlying sales contract entered into between seller and buyer. Evidently, payment for the goods will be made upon compliance of documents instead of compliance of the goods traded. Disputes between trading parties concerning the goods in the underlying contracts are to be addressed using a different cause of action which should not compromise the LC operations and undertaking of the bank to honour payment. Based on this unique characteristic, this paper aims to explain the meaning of principle of autonomy, its nature and background. It highlights the significance of principle of autonomy in LC transaction. Furthermore, it discusses the legal framework of principle of autonomy where to a certain extent, comparisons between relevant articles in the UCP 500 and 600 are highlighted. Next, discussion focuses on relevant case-law where the principle of autonomy was significantly prevailed in LC transaction. Last but not least, it addresses the issue of Shariah compliance in the application of this principle in LC.